Pembangunan Model Elektrokoagulasi Menggunakan Elektroda Aluminium untuk Menurunkan Timbal (Pb) Air Limbah Batik di UKM Batik Nugraha Ngawi - Winarko, Winarko; Suprijandani, Suprijandani; Sugito, Bambang Hadi; Yumni, Hilmi; Nurmayanti, Demes; Wardoyo, Slamet (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
This community service activity is expected to be able to make a real contribution to solving problems that exist in the community, as well as bring the roles and functions of universities closer to the community. Community Service aimed to build an Electrocoagulation Model Using Aluminum Electrodes 20 cm apart at a voltage of 20 Volts, a current of 10 Ampere system back with a contact time of 60 minutes. The Community Service method was through organizing activities and dividing work groups so that all work was evenly distributed. The results of Community Service activities were in the form of an Electrocoagulation Model Building Using Aluminum Electrodes 20 cm apart at a voltage of 20 Volts, a current of 10 Ampere Batch System with a contact time of 60 minutes, the connection of treated wastewater to the Electrocoagulation Model to the sewerage (effluent) and understanding of the operation, performance, maintenance and importance of utilizing wastewater treatment products containing Lead (Pb) for filling fish ponds and watering gardens. It was recommended that the Electrocoagulation Model Using 20 cm Aluminum Electrodes with 20 Volts and a strong current of 10 Ampere used with a contact time of 60 minutes, the power source must be turned off when the electrocoagulation reactor is not in use and the treated water can be used to gardens, yards, and fish pond.